MARKETING STRATEGY ANALYSIS IN CV. KASIH SAYANGIN PANAKKUKANG DISTRICT, MAKASSAR CITY - Fadil Pradana; Abdul Rahman Kadir; Mursalim Nohong (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2023)
The purpose of this study is to analyze marketing strategies for increasing product sales at CV. Kasih Sayang for SMIs in the city of Makassar. This type of research is qualitative research. The data sources of this research are primary and secondary data sources. Data collection techniques used in this study were interviews, observation, and documentation. The data analysis technique used in this study was the data collection stage and the analysis phase using a qualitative descriptive analysis method, namely IFAS, EFAS, and SWOT analysis. The results of the study show that the current marketing strategy is direct marketing and indirect marketing. The results of the company's internal factor analysis using the IFE matrix, the company's main strength is a better taste of the products it produces (score 0.80). The main weakness possessed by CV. Kasih Sayang The interest of SMIs is less innovative packaging design and form (score 0.17). A total score below 2.5 indicates the company's internal position is weak in overcoming existing weaknesses with its strengths. The results of the SWOT analysis produce 12 alternative strategies that can be chosen by companies, namely maintaining product taste and also increasing customer satisfaction and loyalty, maintaining and increasing collaboration with potential partners to increase market share, and maximizing the attractiveness displayed at sales outlets through product variants at low prices. compete, develop the attractiveness of more innovative product packaging so that it is increasingly in demand by consumers and has an image among entrepreneurs, given the amount of production produced so that products that exceed the shelf life limits are not wasted , improve the quality of the resulting chocolate concentration so that the resulting product form can last accordance with the shelf life, Maintaining the consistency of the quality of chocolate products so that they can compete with similar competing products, Maintaining good cooperation with various partners so that the company's activities in the aspects of marketing, production, etc. thinning due to scarcity of raw materials and anticipating the emergence of new competitors, maximizing the packaging power of product packaging so that it remains in demand by consumers and able to compete with similar products, maximizing provisions on quantity and production yields so that products that reach the limit of durability are not wasted and regulates conditions for use raw materials wisely to anticipate the scarcity of raw materials and rising raw materials prices.